Virgil's Aristaeus Epyllion: Georgics 4.315-558 - Belcher, Kenneth L. (My University, 1993)
Virgil's Georgics has been the subject of a daunting number of articles, studies and commentaries. Of the many problems associated with the work perhaps the greatest difficulty has arisen in assessing the Aristaeus epyllion, G. 4.315-558. Numerous attempts have been made to interpret the passage and to explain its connection with the rest of Book 4 and with the whole of the Georgics. Many opinions have been expressed (quot homines, tot sententiae); however, none has been deemed completely satisfactory and none has been universally accepted. I have chosen not to add to the already vast body of scholarship dealing with these issues but to approach the epyllion from a different perspective.
Despite its importance - it is, after all, the only existing extended narrative by Virgil other than the Aeneid, which it predates - the Aristaeus epyllion has not been the subject of a single exhaustive study. I have attempted, therefore, to treat the passage in isolation, tacitly accepting that it is connected with the rest of the work. My study includes a reappraisal (with, I trust, fresh insights) of the relevant mythological background and structure of the piece. Its literary form, the epyllion, is also discussed and a more detailed examination of setting and character than has been undertaken previously is presented. Finally, I offer a detailed critical appreciation in which Virgil's narrative technique, his use of literary models (especially, but not exclusively, Homer) and features of sound, rhythm and diction receive comment.
Keywords: Vergils; Epyllion; Georgics 4.315-558; Classics; Classics